Kinetics of invertase synthesis by Saccharomyces cerevisiae in synthetic medium - Ikram-ul-Haq, Ikram-ul-Haq (2006)
Present investigation deals with optimization of appropriate substrate concentration and incubation temperature both for growth of Saccharomyces cerevisiae and invertase production. Submerged fermentation technique was employed in the present study. The maximal production of invertase during the course of study was achieved after 48 h of incubation using initial sucrose concentration, 15.0 g l-1. The sugar consumption and dry cell mass were also examined. Data was subjected to kinetic analysis and on the basis of kinetic parameters such as Yp/x (amount of enzyme produced mg-1 cell mass), Yp/s (amount of enzyme produced mg-1 sugar consumed), Yx/s (mg cells mg-1 substrate consumed), Ys/x (mg sugar consumed mg-1 cell mass produced), qp (Amount of enzyme produced mg-1 sugar consumed h-1), qs (mg mg-1 cells h-1), qx (mg cells mg-1 sugar consumed h-1), Âµ (mg cells produced h-1), it was found that temperature had a direct influence both on substrate consumption and synthesis of enzyme. Similarly, higher concentrations of sucrose in fermentation medium induced catabolite repression of yeast invertase.